Tactile Perception for Stroke Induce Changes in Electroencephalography - Si-Nae Ahn; Jeong-Weon Lee; Sujin Hwang (SAGE Publishing, 2016)
Objective/Background: Tactile perception is a basic way to obtain and evaluate information about an object. The purpose of this study was to examine the effects of tactile perception on brain activation using two different tactile explorations, passive and active touches, in individuals with chronic hemiparetic stroke. Methods: Twenty patients who were diagnosed with stroke (8 right brain damaged, 12 left brain damaged) participated in this study. The tactile perception was conducted using passive and active explorations in a sitting position. To determine the neurological changes in the brain, this study measured the brain waves of the participants using electroencephalography (EEG). Results: The relative power of the sensory motor rhythm on the right prefrontal lobe and right parietal lobe was significantly greater during the active tactile exploration compared to the relative power during the passive exploration in the left damaged hemisphere. Most of the measured brain areas showed nonsignificantly higher relative power of the sensory motor rhythm during the active tactile exploration, regardless of which hemisphere was damaged. Conclusion: The results of this study provided a neurophysiological evidence on tactile perception in individuals with chronic stroke. Occupational therapists should consider an active tactile exploration as a useful modality on occupational performance in rehabilitation training.